IgE-dependent human basophil responses are inversely associated with the sarcoplasmic reticulum Ca2+-ATPase (SERCA) - Selnø, Anette T. Hansen; Sumbayev, Vadim V.; Gibbs, Bernhard F. (Frontiers in Immunology, 2023)
Basophils crucially contribute to allergies and other Th2-driven diseases by rapidly releasing inflammatory and immunomodulatory mediators following high-affinity IgE-receptor crosslinking. Although these basophil-mediated responses depend on sensitization with antigen-specific IgE, this does not necessarily predict clinical symptom severity. It is thought that the balance of early stimulatory (e.g. SYK) and inhibitory (e.g. SHIP-1) intracellular signals are associated with basophil responsiveness, which is also critically dependent on calcium mobilization. Previous studies suggest that the sarcoplasmic reticulum Ca2+-ATPase (SERCA2), which regulates cytosolic calcium levels, may be inversely associated with airway smooth muscle reactivity in asthma. Since basophils are implicated in asthma severity, our aims were to address whether SERCA2 governs human basophil responses. Human basophils were obtained from buffy coats, following research ethics approval, and further purified by immunomagnetic cell sorting. Expressions of SERCA2, and other isoforms, were determined by Western blotting in parallel to measuring IgE-dependent histamine releases from the same donors. The effects of SERCA-activators and inhibitors were also assessed on their abilities to modulate basophil histamine release. We observed an inverse correlation between basophil responsiveness to IgE-dependent stimulation and SERCA2 expression. Thapsigargin, a highly-specific SERCA inhibitor, stimulated basophil histamine release and potentiated IgE-dependent secretion of the amine. Conversely, disulfiram, a SERCA activator, inhibited IgE-dependent basophil activation. These results indicate that SERCA2 is an additional regulator of basophil reactivity alongside early excitatory or inhibitory signal transduction pathways. Enhancement of SERCA expression or activation pathways could therefore potentially be considered as a novel therapeutic approach for the treatment of basophil-driven pathologies.